Semiotics in Avengers’ Movie: Infinity War and End Game Trailer - Janinta Ginting; Ikhwanuddin Nasution; Thyrhaya Zein (Budapest International Research and Critics University, 2022)
This study purpose is to finding the sign based on theory pioneered by Charles Sanders Peirce. The design of this research is descriptive qualitative research. The method of this study based on the theory of Creswell, that consist of five steps; (1) collected the data; (2) categorize the data; (3) coding the data; (4) the chronological of the data; (5) analyzing the data. The source of the data is Avengers’ Movie Infinity War and End Game that taken from YouTube channel of Marvel Entertainment that downloaded by savefromnet.com. The data is collected by document analysis. The data is the screenshot of the scene in the trailer. This research consists of visual and verbal data which used semiotic icon, index and symbol. In fiction movie, visual data is generally found. The finding of the research is (25) data. Visual data consists of (20) and verbal data consist of (5). One data consist of several semiotic sign. Icon is consisting of (12), Index is consisting of (3), and symbol is consisting of (9). Icon is the dominant element both the trailers. Fiction movie is not interesting without visual effect. But in this case movie trailer also supported by something real, such as the properties and setting for the good quality of the movie.